Teacher-Student Relationships and School Adjustment: Progress and Remaining Challenges - Hughes, Jan N. (2012)
This commentary highlights the ways in which the articles in this special issue contribute to the second generation of research on teacher-student relationships. Second generation research aims to increase our understanding of the development of these relationships, and the processes responsible for their effects, as well as to evaluate theoretically-informed interventions designed to enhance teacher-student interactions. Despite unanswered questions and challenges that confront this field of inquiry, the current state of knowledge is adequate to apply the knowledge gained to the task of increasing teachers’ abilities to provide positive social and emotional learning environments, thereby improving students’ learning and behavioral adjustment.